Forschungsperspektiven zu Sustainable Finance in kleinen und mittleren Unternehmen - Rossmann, Felix Konstantin (ZfKE – Zeitschrift für KMU und Entrepreneurship)

A Two-Stage Approximation Methodology for Efficient DNN Hardware Implementation - Hadipour, Amir Hossein; Jafari, Atousa; Awais, Muhammad; Platzner, Marco (2025 IEEE 28th International Symposium on Design and Diagnostics of Electronic Circuits and Systems (DDECS))

Broadband Nyquist Pulse Generation on TFLN Platform for Integrated Quantum Source - Kress, Christian; Mihaylov, Martin Miroslavov; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (PIERS Proceedings)
The generation of optically broadband Nyquist pulse sequences using an integrated Mach-Zehnder modulator (MZM) in a thin-film lithium-niobate (TFLN) platform with repetition rates of 5 to 32 GHz and optical bandwidths of up to 160 GHz is demonstrated. Nyquist pulse sequences with high optical bandwidth can be used as synchronization and control signals in quantum sources based on photon pair generation.

Beforschung eines MINT Clusters – erste Ergebnisse und weitere Schritte - Reckmann, Eileen; Temmen, Katrin

Revisiting the analysis of references among Common Criteria certified products - Janovsky, Adam; Chmielewski, Łukasz; Svenda, Petr; Jancar, Jan; Matyas, Vashek (Computers & Security)

ROCA and Minerva Vulnerabilities - JANCAR, Jan; SVENDA, Petr; SYS, Marek (Embedded Cryptography 3)

Let’s DOIT: Using Intel’s Extended HW/SW Contract for Secure Compilation of Crypto Code - Arranz-Olmos, Santiago; Barthe, Gilles; Grégoire, Benjamin; Jancar, Jan; Laporte, Vincent; Oliveira, Tiago; Schwabe, Peter (IACR Transactions on Cryptographic Hardware and Embedded Systems)
It is a widely accepted standard practice to implement cryptographic software so that secret inputs do not influence the cycle count. Software following this paradigm is often referred to as “constant-time” software and typically involves following three rules: 1) never branch on a secret-dependent condition, 2) never access memory at a secret-dependent location, and 3) avoid variable-time arithmetic operations on secret data. The third rule requires knowledge about such variable-time arithmetic instructions, or vice versa, which operations are safe to use on secret inputs. For a long time, this knowledge was based on either documentation or microbenchmarks, but critically, there were never any guarantees for future microarchitectures. This changed with the introduction of the data-operand-independent-timing (DOIT) mode on Intel CPUs and, to some extent, the data-independent-timing (DIT) mode on Arm CPUs. Both Intel and Arm document a subset of their respective instruction sets that are intended to leak no information about their inputs through timing, even on future microarchitectures if the CPU is set to run in a dedicated DOIT (or DIT) mode.In this paper, we present a principled solution that leverages DOIT to enable cryptographic software that is future-proof constant-time, in the sense that it ensures that only instructions from the DOIT subset are used to operate on secret data, even during speculative execution after a mispredicted branch or function return location. For this solution, we build on top of existing security type systems in the Jasmin framework for high-assurance cryptography.We then use our solution to evaluate the extent to which existing cryptographic software built to be “constant-time” is already secure in this stricter paradigm implied by DOIT and what the performance impact is to move from constant-time to future-proof constant-time.

ECTester: Reverse-engineering side-channel countermeasures of ECC implementations - Suchanek, Vojtech; Jancar, Jan; Kvapil, Jan; Svenda, Petr; Chmielewski, Łukasz (IACR Transactions on Cryptographic Hardware and Embedded Systems)
Developers implementing elliptic curve cryptography (ECC) face a wide range of implementation choices created by decades of research into elliptic curves. The literature on elliptic curves offers a plethora of curve models, scalar multipliers, and addition formulas, but this comes with the price of enabling attacks to also use the rich structure of these techniques. Navigating through this area is not an easy task and developers often obscure their choices, especially in black-box hardware implementations. Since side-channel attackers rely on the knowledge of the implementation details, reverse engineering becomes a crucial part of attacks.This work presents ECTester – a tool for testing black-box ECC implementations. Through various test suites, ECTester observes the behavior of the target implementation against known attacks but also non-standard inputs and elliptic curve parameters. We analyze popular ECC libraries and smartcards and show that some libraries and most smartcards do not check the order of the input points and improperly handle the infinity point. Based on these observations, we design new techniques for reverse engineering scalar randomization countermeasures that are able to distinguish between group scalar randomization, additive, multiplicative or Euclidean splitting. Our techniques do not require side-channel measurements; they only require the ability to set custom domain parameters, and are able to extract not only the size but also the exact value of the random mask used. Using the techniques, we successfully reverse-engineered the countermeasures on 13 cryptographic smartcards from 5 major manufacturers – all but one we tested on. Finally, we discuss what mitigations can be applied to prevent such reverse engineering, and whether it is possible at all.

On the complexity of estimating ground state entanglement and free energy - Gharibian, Sevag; Kamminga, Jonas (arXiv:2510.06796)
Understanding the entanglement structure of local Hamiltonian ground spaces is a physically motivated problem, with applications ranging from tensor network design to quantum error-correcting codes. To this end, we study the complexity of estimating ground state entanglement, and more generally entropy estimation for low energy states and Gibbs states. We find, in particular, that the classes qq-QAM [Kobayashi, le Gall, Nishimura, SICOMP 2019] (a quantum analogue of public-coin AM) and QMA(2) (QMA with unentangled proofs) play a crucial role for such problems, showing: (1) Detecting a high-entanglement ground state is qq-QAM-complete, (2) computing an additive error approximation to the Helmholtz free energy (equivalently, a multiplicative error approximation to the partition function) is in qq-QAM, (3) detecting a low-entanglement ground state is QMA(2)-hard, and (4) detecting low energy states which are close to product states can range from QMA-complete to QMA(2)-complete. Our results make progress on an open question of [Bravyi, Chowdhury, Gosset and Wocjan, Nature Physics 2022] on free energy, and yield the first QMA(2)-complete Hamiltonian problem using local Hamiltonians (cf. the sparse QMA(2)-complete Hamiltonian problem of [Chailloux, Sattath, CCC 2012]).

Understanding personal agency through metaphor, or Why academic writing is (not) like a roller-coaster ride - Karsten, Andrea (Frontiers in Language Sciences)
Building on and methodologically extending conceptual metaphor theory, the article examines how personal agency as a discursively produced sociopsychological phenomenon can be studied in elicited metaphors through a discourse-analytical approach. More concretely, the study illustrates how early-career researchers experience and express their agency in research writing through personal metaphors of academic writing such as riding a roller coaster or baking a wedding cake. A two-step discursive analysis adapts Hopper and Thompson's multidimensional approach to linguistic transitivity to study agency in language. The analytical approach involves both an in-depth parametrized analysis of all metaphors in the sample and a qualitative cross-analysis of the data. The results show that the participants' metaphors reflect both nuanced personal experiences and cultural expectations of academic writing, the writer, and the text. This emphasizes that research writing is not only a highly subjective practice but also one that is socially and culturally influenced. The article argues that research on agency thus needs elaborate methodological tools to trace discursive and sociopsychological trajectories of complex socio-cognitive practices like academic writing. This has implications not only for the nexus of research writing, identity, and academic enculturation but also for other fields focusing on agency in language.

Annotation Schemes Project A02 "Monitoring the understanding of explanations" - Lazarov, Stefan Teodorov; Türk, Olcay; Grimminger, Angela; Wagner, Petra; Buschmeier, Hendrik

Understanding personal agency through metaphor, or Why academic writing is (not) like a roller-coaster ride - Karsten, Andrea Ramona (Frontiers in Language Sciences)
Building on and methodologically extending conceptual metaphor theory, the article examines how personal agency as a discursively produced sociopsychological phenomenon can be studied in elicited metaphors through a discourse-analytical approach. More concretely, the study illustrates how early-career researchers experience and express their agency in research writing through personal metaphors of academic writing such as riding a roller coaster or baking a wedding cake. A two-step discursive analysis adapts Hopper and Thompson's multidimensional approach to linguistic transitivity to study agency in language. The analytical approach involves both an in-depth parametrized analysis of all metaphors in the sample and a qualitative cross-analysis of the data. The results show that the participants' metaphors reflect both nuanced personal experiences and cultural expectations of academic writing, the writer, and the text. This emphasizes that research writing is not only a highly subjective practice but also one that is socially and culturally influenced. The article argues that research on agency thus needs elaborate methodological tools to trace discursive and sociopsychological trajectories of complex socio-cognitive practices like academic writing. This has implications not only for the nexus of research writing, identity, and academic enculturation but also for other fields focusing on agency in language.

Local Deformation and Failure of Composites during Self-Piercing Riveting: A CT-Based Microstructure Investigation - Dargel, Alrik; Gröger, Benjamin; Schlichter, Malte Christian; Gerritzen, Johannes; Köhler, Daniel; Meschut, Gerson; Gude, Maik; Kupfer, Robert (Proceedings of the 8th International Conference on Integrity-Reliability-Failure (IRF2025))
The use of continuous fiber-reinforced thermoplastics (FRTP) in automotive industry increases due to their excellent material properties and possibility of rapid processing. The scale spanning heterogeneity of their material structure and its influence on the material behavior, however, presents significant challenges for most joining technologies, such as self-piercing riveting (SPR). During mechanical joining, the material structure is significantly altered within and around the joining zone, heavily influencing the material behavior. A comprehensive understanding of the underlying phenomena of material alteration during the SPR process is essential as basis for validating numerical simulations. This study examines the material structure at ten stages of a step-setting test of SPR with two FRTP sheets with glass-fiber reinforcement. Utilizing X-ray computed tomography (CT), the damage phenomena within different areas of the setting test are analyzed three-dimensionally and key parameters are quantified. Dominating phenomena during the penetration of the rivet into the laminate are fiber failure (FF), interfiber failure (IFF) and fiber bending, while delamination, fiber kinking and roving splitting are also observed. At the final stages, the bottom layers of the second sheet collapse and form a bulge into the cavity of the die.
Keywords: self-piercing riveting; computed tomography; thermoplastic composites; process-structure-interaction

A Quantitative Guide to Navigate Speed/Accuracy Tradeoffs in System Level Design of RISC-V Processor Grids - Luchterhandt, Lars; Govindasamy, Vivek; Wang, Yutong; Scheytt, Christoph; Mueller, Wolfgang; Dömer, Rainer (2025 Forum on Specification & Design Languages (FDL))

Land und Nation: Perspektiven vergleichender Forschung in ausgewählten Diskursen der Zeitschrift Tertium Comparationis - Freitag, Christine (Tertium Comparationis)
Dieser Artikel spiegelt die dreißigjährige Geschichte der Zeitschrift Tertium Comparationis, indem er eine der zentralen Vergleichseinheiten Vergleichender Erziehungswissenschaft in den Blick nimmt. Themenhefte und Einzelbeiträge der Zeitschrift Tertium Comparationis haben über die Jahrzehnte immer wieder reflexive Blicke auf die Vergleichseinheit Land und/oder Nation geworfen, aber auch – ohne Bezüge zu solchen Diskursen – Länder- und Nationenvergleiche in unterschiedlichen Vorgehensweisen präsentiert. Bei der intensiven und analytischen Lektüre der Themen und Inhalte ergeben sich Cluster der Perspektivsetzungen und damit verbundene Diskurse, von denen einige aufgrund ihrer Häufigkeit und Intensität besonders relevant erscheinen. Die aufzufindenden Diskurse und Cluster werden im Beitrag präsentiert und anhand normativer, kritischer und innovativer Beiträge verifiziert. Trotz konstant wiederholter Kritik und konzeptueller Änderungen, bleiben Land und Nation zentrale Kategorien Vergleichender Erziehungswissenschaft.
Keywords: Tertium Comparationis; Land; Nation; Vergleichende Erziehungswissenschaft; Diskurse

Die Menschheitsfamilie und der Begriff der Umma – Islamische Perspektiven im interreligiösen Dialog - Abdelrahem, Mohammed

"Komparative Theologie und Soziale Arbeit?!" - Lebock, Sarah
BloKK-Beitrag für das ZeKK, 11.07.2025

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Analysis of the binding mechanisms depending on versatile process variants of self-piercing riveting - Lüder, Stephan; Holtkamp, Pia Katharina; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson; Lechner, Michael; Schmale, Hans Christian (Materials Research Proceedings)
The constantly increasing demand for climate protection and resource conservation requires innovative and versatile joining processes that improve adaptability to the joining task and robustness to enable flexible manufacturing on a production line. Therefore, the versatile SPR (V-SPR) and tumbling SPR (T-SPR) were developed. Using the example of a mixed material combination HCT590X+Z (t0 = 1.0 mm) / EN AW-6014 T4 (t0 = 2.0 mm), these processes were examined and compared with regard to the binding mechanisms form closure and force closure using micrographs, non-destructive resistance measurements and destructive torsion tests. For this purpose, a new sample geometry was defined, and the methods were adapted to the SPR process variants.
Keywords: Joining; Self-Piercing Riveting; Sheet Metal

Validation and Verification of Novel Three-Dimensional Crack Growth Simulation Software GmshCrack3D - Krome, Sven; Duffe, Tobias; Kullmer, Gunter; Schramm, Britta; Ostwald, Richard (Applied Sciences)
The accurate prediction of crack initiation and propagation is essential for assessing the structural integrity of mechanically joined components and other complex assemblies. To overcome the limitations of existing finite element tools, a modular Python framework has been developed to automate three-dimensional crack growth simulations. The program combines geometric reconstruction, adaptive remeshing, and the numerical evaluation of fracture mechanics parameters within a single, fully automated workflow. The framework builds on open-source components and remains solver-independent, enabling straightforward integration with commercial or research finite element codes. A dedicated sequence of modules performs all required steps, from mesh separation and crack insertion to local submodeling, stress and displacement mapping, and iterative crack-front update, without manual interaction. The methodology was verified using a mini-compact tension (Mini-CT) specimen as a benchmark case. The numerical results demonstrate the accurate reproduction of stress intensity factors and energy release rates while achieving high computational efficiency through localized refinement. The developed approach provides a robust basis for crack growth simulations of geometrically complex or residual stress-affected structures. Its high degree of automation and flexibility makes it particularly suited for analyzing cracks in clinched and riveted joints, supporting the predictive design and durability assessment of joined lightweight structures.